2013
DOI: 10.1371/journal.pone.0062061
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gender, Process of Care Measures, and Outcomes in ACS in India: Results from the Detection and Management of Coronary Heart Disease (DEMAT) Registry

Abstract: BackgroundStudies from high-income countries have shown that women receive less aggressive diagnostics and treatment than men in acute coronary syndromes (ACS), though their short-term mortality does not appear to differ from men. Data on gender differences in ACS presentation, management, and outcomes are sparse in India.Methods and ResultsThe Detection and Management of Coronary Heart Disease (DEMAT) Registry collected data from 1,565 suspected ACS patients (334 women; 1,231 men) from ten tertiary care cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
53
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 23 publications
14
53
4
Order By: Relevance
“…The mean age of our study population was 66 years, which was slightly older than reported in other LIMCs including Egypt [11], China [12], Thailand [13], and India [14]. In our study, women were, on average, 6 years older than men, which is comparable with prior findings reported from China [12], Thailand [13], Egypt [11] and India [14] in which women were, on average, several years older than men.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The mean age of our study population was 66 years, which was slightly older than reported in other LIMCs including Egypt [11], China [12], Thailand [13], and India [14]. In our study, women were, on average, 6 years older than men, which is comparable with prior findings reported from China [12], Thailand [13], Egypt [11] and India [14] in which women were, on average, several years older than men.…”
Section: Discussionsupporting
confidence: 83%
“…The death rates reported in GRACE were lower than have been observed in most studies in LMICs [11]–[13], [27] with the exception of India [14]; this may be due to the fact that patients from the GRACE study were mainly from high income countries. On the other hand, data from the Gulf Registry of Acute Coronary Syndrome (Gulf RACE), which included more than 8,000 patients with ACS from 6 Middle East countries in 2007, indicated that women experienced a higher risk for dying during hospitalization than men (14% vs. 5%) even after adjustment for potential confounding factors [23].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…115 Observational studies do suggest that, to a large extent, the in-hospital treatment of ACS in LMICs includes the use of aspirin, ACE inhibitors, and beta blockers. 95,98,116-118 The ACCESS Study, a prospective observational registry of patients hospitalized for ACS between 2007 and 2008 in 19 LMICs, found that aspirin and lipid-lowering therapies were each given to more than 90% of patients, while uptake of beta-blockers and ACE inhibitors were at 78% and 68%, respectively. 116 However, comparison of countries participating in the OASIS registries found lower use of heparin in LMICs than in HICs, while the ACCESS investigators found that only 39% of patients presenting with ST-elevation myocardial infarction received fibrinolysis.…”
Section: Acs and Ihd Burden In Lmicsmentioning
confidence: 99%
“…In pre-existing large acute coronary syndromes (ACS) registries in India (CREATE [Treatment and Outcomes of Acute Coronary Syndromes in India] and OASIS-2 [Organization to Assess Strategies for Ischemic Syndromes Trial]), little has been described regarding sex differences in these patients [3,4]. The DEMAT (Detection and Management of Acute Coronary Events) registry of 1,565 ACS patients from 10 tertiary care centers in India demonstrated that after adjustment for age, education, history of coronary heart disease, ST-segment elevation myocardial infarction (STEMI) presentation, or reperfusion of any type, there was no evidence of an effect of increased risk of death at 30 days among women compared with men, nor was there any difference between death, rehospitalization, and cardiac arrest at 30 days [5]. However, literature from high-income countries (HIC) has repeatedly shown that sex differences do exist in the presentation, diagnostics, and therapeutic management of ACS patients [610].…”
mentioning
confidence: 99%